Let us solve the equation:
"\\frac{d^2y}{dx^2}-2\\frac{dy}{dx}=e^x \\sin x"
The characteristic equation of the homogeneous equation is the following:
"k^2-2=0"
Therefore, "k_1=-\\sqrt{2}, k_2=\\sqrt{2}" .
According to the method of variation of parameter, the differential equation has the following solution:
"y(x)=C_1(x)e^{-\\sqrt{2}x}+ C_2(x)e^{\\sqrt{2}x}" .
For functions "C_1(x)" and "C_2(x)" we have the following system for their derivatives:
"\\begin{cases} C_1'(x)e^{-\\sqrt{2}x}+ C_2'(x)e^{\\sqrt{2}x} =0\\\\ -\\sqrt{2} C_1'(x)e^{-\\sqrt{2}x}+\\sqrt{2} C_2'(x)e^{\\sqrt{2}x} =e^x\\sin x \\end{cases}"
"\\begin{cases} C_1'(x)e^{-\\sqrt{2}x}+ C_2'(x)e^{\\sqrt{2}x} =0\\\\ -C_1'(x)e^{-\\sqrt{2}x}+ C_2'(x)e^{\\sqrt{2}x} =\\frac{1}{\\sqrt{2}}e^x\\sin x \\end{cases}"
"\\begin{cases} C_1'(x)e^{-\\sqrt{2}x}+ C_2'(x)e^{\\sqrt{2}x} =0\\\\ 2C_2'(x)e^{\\sqrt{2}x} =\\frac{1}{\\sqrt{2}}e^x\\sin x \\end{cases}"
"\\begin{cases} C_1'(x)=- C_2'(x)e^{2\\sqrt{2}x} =0\\\\ C_2'(x) =\\frac{1}{2\\sqrt{2}}e^{(1-\\sqrt{2})x}\\sin x \\end{cases}"
"\\begin{cases} C_1'(x)=- \\frac{1}{2\\sqrt{2}}e^{(1+\\sqrt{2})x}\\sin x \\\\ C_2'(x) =\\frac{1}{2\\sqrt{2}}e^{(1-\\sqrt{2})x}\\sin x \\end{cases}"
In the sequel we use the well known formula:
"\\int e^{ax}\\sin (bx) dx =\\frac{b^2e^{ax}(a\\sin(bx)-b\\cos(bx))}{a^2(a^2+b^2)}+C"
"C_1(x)=-\\frac{1}{2\\sqrt{2}}\\frac{e^{(1+\\sqrt{2})x}((1+\\sqrt{2})\\sin(x)-\\cos(x))}{(1+\\sqrt{2})^2((1+\\sqrt{2})^2+1)}+C_1=-\\frac{1}{2\\sqrt{2}}\\frac{e^{(1+\\sqrt{2})x}((1+\\sqrt{2})\\sin(x)-\\cos(x))}{(3+2\\sqrt{2})(4+2\\sqrt{2})}+C_1="
"=-\\frac{1}{2\\sqrt{2}}\\frac{e^{(1+\\sqrt{2})x}((1+\\sqrt{2})\\sin(x)-\\cos(x))}{20+14\\sqrt{2}}+C_1\n=-\\frac{e^{(1+\\sqrt{2})x}((1+\\sqrt{2})\\sin(x)-\\cos(x))}{56+40\\sqrt{2}}+C_1"
"C_2(x)=\\frac{1}{2\\sqrt{2}}\\frac{e^{(1-\\sqrt{2})x}((1-\\sqrt{2})\\sin(x)-\\cos(x))}{(1-\\sqrt{2})^2((1-\\sqrt{2})^2+1)}+C_2=\n\\frac{1}{2\\sqrt{2}}\\frac{e^{(1-\\sqrt{2})x}((1-\\sqrt{2})\\sin(x)-\\cos(x))}{(3-2\\sqrt{2})(4-2\\sqrt{2})}+C_2="
"=\\frac{1}{2\\sqrt{2}}\\frac{e^{(1-\\sqrt{2})x}((1-\\sqrt{2})\\sin(x)-\\cos(x))}{20-14\\sqrt{2}}+C_2=\n\\frac{e^{(1-\\sqrt{2})x}((1-\\sqrt{2})\\sin(x)-\\cos(x))}{-56+40\\sqrt{2}}+C_2"
Consequently, the solution is the following:
"y(x)=(-\\frac{e^{(1+\\sqrt{2})x}((1+\\sqrt{2})\\sin(x)-\\cos(x))}{56+40\\sqrt{2}}+C_1)e^{-\\sqrt{2}x}+ (\\frac{e^{(1-\\sqrt{2})x}((1-\\sqrt{2})\\sin(x)-\\cos(x))}{-56+40\\sqrt{2}}+C_2)e^{\\sqrt{2}x}"
Comments
Leave a comment